1999
DOI: 10.1073/pnas.96.22.12367
|View full text |Cite
|
Sign up to set email alerts
|

Identification and reconstitution of the origin recognition complex from Schizosaccharomyces pombe

Abstract: The origin recognition complex (ORC), first identified in Saccharomyces cerevisiae (sc), is a six-subunit protein complex that binds to DNA origins. Here, we report the identification and cloning of cDNAs encoding the six subunits of the ORC of Schizosaccharomyces pombe (sp). Sequence analyses revealed that spOrc1, 2, and 5 subunits are highly conserved compared with their counterparts from S. cerevisiae, Xenopus, Drosophila, and human. In contrast, both spOrc3 and spOrc6 subunits are poorly conserved. As repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
67
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 28 publications
5
67
0
1
Order By: Relevance
“…This idea suggests that the N-terminal region of spOrc4p, even when complexed with the other spOrc subunits, may be exposed. This notion is in keeping with the finding that the five-subunit complex, devoid of spOrc4p, is converted to the six-subunit complex upon addition of spOrc4p (19,20).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This idea suggests that the N-terminal region of spOrc4p, even when complexed with the other spOrc subunits, may be exposed. This notion is in keeping with the finding that the five-subunit complex, devoid of spOrc4p, is converted to the six-subunit complex upon addition of spOrc4p (19,20).…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies showed that spORC binding to different origin sequences is mediated solely through the N-terminal AT-hook domains of Orc4p and that these interactions were not dependent on ATP (7,(18)(19)(20). A stable five-subunit spORC lacking Orc4p has been isolated as well as a six-subunit spORC containing an Orc4p derivative devoid of the N-terminal AT-hook domains (7,19,20). Such spORC derivatives do not bind to sp origin DNAs.…”
mentioning
confidence: 99%
“…The presence of these multiple AT-hook motifs suggests that the binding of spORC to origin DNA is likely to be influenced by this domain. Although all the spORC subunits have been identified and the complex has been reconstituted from in vitro transcription and translation products of each subunit (17), the origin DNAbinding properties of spORC have not been examined as yet.…”
Section: Na Replication Origin Sequences In Saccharomyces Cerevisiaementioning
confidence: 99%
“…ORC binds to replication origin DNA throughout the cell cycle and is required to recruit other essential initiation factors for the assembly of the prereplicative complex (15,16). ORC is conserved in all eukaryotes and has been identified and purified from other species, including S. pombe, Drosophila melanogaster, Xenopus laevis, and humans (17)(18)(19)(20)(21)(22). Although in vivo and in vitro studies suggest that ORC is essential for DNA replication in these species (15,16), the interactions between these ORCs and their replication origin DNAs have not been characterized except for Sac.…”
mentioning
confidence: 99%
“…In S. cerevisiae, Orc6 is not important for DNA binding, but it is required for cell survival (10)(11)(12) and the maintenance of the pre-RC, specifically for recruitment of Cdt1 followed by MCM loading (13,14). Schizosaccharomyces pombe and metazoan Orc6 proteins (6,15,16) are more homologous, similar in size, and considerably smaller than the S. cerevisiae Orc6. In Drosophila, Orc6 is essential for ORC-dependent DNA binding and DNA replication (17,18).…”
mentioning
confidence: 99%